Evaluation of artificial reefs in West Coast, Malaysia - Ismail, Illisriyani; Mohd. Noh, Kusairi; Mohamed Arshad, Fatimah; Mohd. Noh, Aswani Farhana (2009)
The use of artificial reefs in Malaysia is relatively new and if properly constructed, artificial reefs (ARs) can enhance fish habitat and easier access to quality fishing grounds and improved quality of catch will benefit fishermen and coastal communities. The first ARs were built in year 1975 by Department of Fisheries Malaysia and now there are more than 250 ARs were built in Malaysia. This paper examines the economic return of artificial reefs on the fishermen and the industry in West Coast (states of Kedah, Perak and Melaka) of Peninsular Malaysia, which are to assess the influence of these ARs on the fisheries and the impact of income changes on the socioeconomics conditions of fisher-folk fishing at ARs. In the middle of 2007 and early 2008, a survey has been carried out to evaluate artificial reefs in the states within a period of 10 months (from April 2007 until January 2008) and with a sample size of 7 boats in Kedah, 20 boats in Perak and 7 boats in Melaka. To analyze the collected data, the descriptive analyses which have been applied are catch analysis, operation cost, profitability operation analysis and cost-benefit analysis have been done to describe the information of the quantity of catch, value of catch, cost of catch, profit and the income of the fishers. From the results, Perak has the highest fish landing which is 30,819.35 kg, followed by Melaka (11,252.23 kg) and Kedah (11,190.50 kg). The average incomes of the three states are between MYR100-MYR400 per month and the state that gained highest income is Kedah which is MYR405.79. The percentage of operation cost is referring to the difference between profit and the income of the fishermen. The overall findings suggest that the deployment of ARs is one of an effective way in helping the fishers’ income and their profitability.